Loop Regulation Between microRNAs and Epigenetics Underlie microRNA Dysregulation in Multiple Myeloma and Is Associated with the Disease Progression - Kimura, Kei; Kuroda, Yuko; Masuda, Yuta; Yamane, Arito; Hattori, Hikaru; Tahara, Kenichi; Kaneko, Ayaka; Suda, Itsumi; Takahashi, Noriyuki; Gotoh, Nanami; Nagai, Kie; Nagashima, Tomomi; et al. (Blood, 2015)
Background: MicroRNAs (miRs) are small non-coding RNAs of 19-25 bases in length that have the ability to modulate gene expression. Some miRs are involved in carcinogenesis and act as tumor suppressor genes (TSG). It has been shown that epigenetics and miRs play an important role in multiple myeloma (MM) progression; however, precise mechanism underlying miR dysregulation has not yet been fully elucidated. Transcriptional silencing of TSG in cancer cells is often associated with DNA methylation and carried out by DNMTs. miR-29 family directly targets DNMTs and promoters of miR-34 family are also methylated in cancers. In this study, we attempted to clarify the interaction between miR and epigenetics focusing on the miR-29 and miR-34 families and their associated genes to understand mechanism of miR dysregulation in MM. Methods: Bone marrow plasma cells from 123 MM patients, 57 MGUS patients, 20 control subjects and 9 MM cell lines were analyzed. This study was approved by the IRB of Gunma University and all patients provided their informed consent prior to enrollment. MiRs and their target gene mRNA values were determined by RQ-PCR. DNA methylation status was determined by methylation-specific PCR. Decitabine, nutlin-3, c-myc inhibitor 10058-F4, and miRNA-mimicTM were used. Result: We found a significantly reduced expression of miR-29a, -29b, -29c, -34a, -34b, and -34c in MM patients compared with MGUS patients and the control subjects (all: p<0.001). DNMT1, -3A and -3B were elevated in MM patients compared with MGUS patients and the control subjects (p<0.001, p<0.001, p=0.01, respectively). DNMT1 was inversely correlated with miR-29a and miR-29b (r=-0.419, p=0.005, r=-0.407, p=0.006, respectively). DNMT3A was inversely correlated with miR-29a, miR-29b and miR-29c (r=-0.315, p=0.04; r=-0.371, p=0.01; r=-0.315, p=0.04, respectively). DNMT3B was inversely correlated with miR-29a and miR-29b (r=-0.353, p=0.02; r=-0.358, p=0.02, respectively). The promoter regions of miR-34a and miR-34b/c were methylated in the MM cell lines, and the rate of methylation of these miRs were higher in MM patients (45.4%, 70.2%, respectively) compared with MGUS patients (15.8%, 26.3%, respectively) (p<0.001). There were significant positive correlations among the miRs expression levels: 29a-34a r=0.448, p<0.001; 29a-34b r=0.309, p=0.001; 29b-34a r=0.500, p<0.001; 29b-34b r=0.297, p=0.002). The expression level of TP53 and its downstream target p21 was higher in MM patients (p=0.004, p<0.001) compared with MGUS patients and the control subjects. The expression level of TP53 was positively correlated with p21 (r=0.33, p<0.001), but not with miR-34a, -b or -c, which were presumed to be upregulated by TP53. In the MM cell lines, nutlin-3, which accumulates TP53 protein, did not increase the expression of miR-34a, -b or -c; however, decitabine increased the expression of pri-miR-34a by 1.2-7.3 fold, pri-miR-34b by 3.3-7.1 fold and increased miR-34a and miR-34b/c by 1.3-2.3 fold and 1.2-5.4 fold, respectively, suggesting that miR-34 family transcription was suppressed by methylation. The transfection of miR-29a or -29b reduced DNMT3A and 3B expression by 0.5 fold and increased pri-miR-34 expression by 2-8 fold. Treatment with a c-myc inhibitor increased the expression of pri-miR-29a/b-1 by 6-8 fold, and miR-29b by 4-7 fold in the MM cell lines. Moreover, the c-myc inhibitor increased the expression of pri-miR-34a by 20-192 fold and miR-34a by 3-6 fold. The transfection of miR-34 reduced the expression of target genes CDK6, SIRT1 and c-myc by 0.4 to 0.6 fold. The expression levels of CDK6, SIRT1 and c-myc were significantly higher in MM patients compared with MGUS patients and the control subjects (p=0.04, p<0.0001, p<0.0001, respectively). Conclusion: We found a significant reduction in the miRs expression levels in MM patients and cell lines, which was partly associated with methylation. Correlations between miRs and related transcripts in patients and an in vitro study demonstrate a negative regulation loop where c-myc suppresses the expression of the miR-29 family, the miR-29 family suppresses DNMT, DNMT suppresses the miR-34 family through promoter methylation, and the miR-34 family suppresses c-myc. This mechanism might underlie the dysregulation of miRs in MM and the disruption of this loop mechanism may be a novel target for MM treatment. No relevant conflicts of interest to declare.